Strength of Fibrous Composites - Huang, Zheng-Ming.; Zhou, Ye-Xin.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
"Strength of Fibrous Composites" addresses evaluation of the strength of a fibrous composite by using its constituent material properties and its fiber architecture parameters. Having gone through the book, a reader is able to predict the progressive failure behavior and ultimate strength of a fibrous laminate subjected to an arbitrary load condition in terms of the constituent fiber and matrix properties, as well as fiber geometric parameters. The book is useful to researchers and engineers working on design and analysis for composite materials. Dr. Zheng-Ming Huang is a professor at the School of Aerospace Engineering & Applied Mechanics, Tongji University, China. Mr. Ye-Xin Zhou is a PhD candidate at the Department of Mechanical Engineering, the University of Hong Kong, China.
Keywords: Engineering; Materials; Astronautics; Engineering; Aerospace Technology and Astronautics; Ceramics, Glass, Composites, Natural Methods; Continuum Mechanics and Mechanics of Materials